Peran seni bela diri Silek Pauh dalam menanamkan nilai moral di kalangan generasi muda: - Fathihah Resky Zalia; Tetti Eka Purnama; Junaidi Indrawadi; Monica Tiara (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to analyze the role of the traditional martial art Silek Pauh in instilling moral values among young people, with a focus on the values of discipline and self-control that influence social behavior. This study uses a qualitative approach with a descriptive research design and was conducted at Sanggar Ranah Tigo Raso, Pauh District, Padang City. Research informants were determined through purposive sampling, consisting of Silek Pauh trainers, training participants, participants’ parents, community leaders, youth, and local residents. Data collection was carried out through observation, interviews, and documentation studies. Data validity was tested through technique triangulation, while data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that Silek Pauh plays a role as an effective form of non-formal education in shaping the moral values of young people. The values of discipline and self-control are instilled in a structured and sustainable manner through adherence to training rules, trainers’ role modeling, habituation of attitudes, as well as the internalization of Minangkabau customary values and philosophy. This process encourages the formation of responsible attitudes, the ability to manage emotions, and social awareness, which are reflected in participants’ behavior in family and community environments. These findings affirm that Silek Pauh has a significant contribution in supporting the development of young people’s character based on local cultural values.